Low Ca diet leads to increased Ca retention by changing the gut flora and ileal pH value in laying hens - Sha Jiang; Xinyu Zou; Miao Mao; Mi Zhang; Wenjun Tu; Meilan Jin (Animal Nutrition, 2023)
Osteoporosis is a common degenerative metabolic bone disease in caged laying hens. Intensive egg production mobilizing large amounts of Ca from bone for eggshell formation, consequently leading to Ca deficiency, has been recognized as a critical factor causing osteoporosis in commercial laying hens. The aim of this study was to examine the effect of Ca deficiency on the function of the gut microbiota–bone axis and related egg production traits and bone health in laying hens. Twenty-four 48-week-old laying hens were fed a control diet (Control, 3.72%) or a low Ca diet (LC, 2.04%) for 60 d (n = 12). Compared to the Control hens, the LC hens had higher levels of alkaline phosphatase and tartrate resistant acid phosphatase (P < 0.05) with lower bone strength, eggshell thickness, and eggshell strength (P < 0.05). In addition, the LC hens had higher plasma estradiol concentrations, while having lower concentrations of interleukin-1 (IL-1) and IL-6. The LC hens also had a lower pH value in the ileum with an increased Ca retention. The principal co-ordinates analysis showed significantly separate cecal microbiota populations between the Control and LC hens. The Prevotellaceae_UCG-001, Subdoligranulum, Peptococcus, and Eubacterium_hallii_group (P < 0.05) were higher, while the CHKC1001 and Sutterella (P < 0.05) were lower at the genus level in the LC hens. In addition, Prevotellaceae_UCG-001, Subdoligranulum and Eubacterium_hallii_group had a negative correlation, while Sutterella was positively correlated with ileal pH values. The transcriptome analysis revealed that the low Ca diet caused 20 and 31 genes to be significantly up- and down-regulated, respectively. The gene expressions of cystic fibrosis transmembrane conductance regulator, solute carrier family 26 member 3 of the anion exchangers, and mitogen-activated protein kinase 12 of pro-inflammatory factors were lower in the LC birds, which was correlated with the lower ileal pH values. These results suggest that the hens with low Ca diet-induced osteoporosis have an increased intestinal Ca retention with a decreased ileal pH value, correlated with the changes in Prevotellaceae_UCG-001, Subdoligranulum, and Eubacterium_hallii_group of beneficial genera. The results provide insights for further understanding and preventing osteoporosis in laying hens.